2018
DOI: 10.1002/jia2.25173
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative research on community experiences in large HIV research trials: what have we learned?

Abstract: IntroductionVery few pragmatic and community‐level effectiveness trials integrate the use of qualitative research over all stages of the trial, to inform trial design, implementation optimization, results interpretation and post‐trial policy recommendations. This is despite the growing demand for mixed methods research from funding agencies and awareness of the vital importance of qualitative and mixed methods research for understanding trial successes and challenges.DiscussionWe offer examples from work we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…We found that stable patients enrolled in community models feared a detachment from health facilities and felt that they would not receive comprehensive care and treatment in the event of opportunistic infections such as tuberculosis if they remained in community-based models owing to their being categorized as 'stable'. Previous studies have highlighted the psycho-social satisfaction patients derive from engaging with health workers on a regular basis [33]. Adjetey and colleagues [17] in a study in Ghana report that patients preferred facility-based HIV services to community-based care even after the government there had invested considerably in the latter models.…”
Section: Discussionmentioning
confidence: 99%
“…We found that stable patients enrolled in community models feared a detachment from health facilities and felt that they would not receive comprehensive care and treatment in the event of opportunistic infections such as tuberculosis if they remained in community-based models owing to their being categorized as 'stable'. Previous studies have highlighted the psycho-social satisfaction patients derive from engaging with health workers on a regular basis [33]. Adjetey and colleagues [17] in a study in Ghana report that patients preferred facility-based HIV services to community-based care even after the government there had invested considerably in the latter models.…”
Section: Discussionmentioning
confidence: 99%
“…Along similar lines, a fundamental change in the publishing bias of medical journals which favours brief quantitative articles is needed to bring method-neutral and transdisciplinary approaches to public health evaluation research [71]. In 2016, the current bias towards publishing quantitative articles led to an open letter to the British Medical Journal calling for it to “move beyond a ‘quantitative strong, qualitative weak’ stance” and to stop “rejecting qualitative research on the grounds of low priority” [72] (page 2).…”
Section: Discussionmentioning
confidence: 99%
“…We found that stable patients enrolled in community models feared a detachment from health facilities and felt that they would not receive comprehensive care and treatment in the event of opportunistic infections such as tuberculosis if they remained in community-based models owing to their being categorized as 'stable'. Previous studies have highlighted the psycho-social satisfaction patients derive from engaging with health workers on a regular basis [33]. Adjetey and colleagues [18] in a study in Ghana report that patients preferred facility-based HIV services to community-based care even after the government there had invested considerably in the latter models.…”
Section: Patientsmentioning
confidence: 99%